The European Rare Kidney Disease Registry (ERKReg): objectives, design and initial results - Bassanese, Giulia; Wlodkowski, Tanja; Servais, Aude; Heidet, Laurence; Roccatello, Dario; Emma, Francesco; Levtchenko, Elena; Ariceta, Gema; Bacchetta, Justine; Capasso, Giovambattista; Jankauskiene, Augustina; Miglinas, Marius; et al. (Orphanet journal of rare diseases, 2021)
The European Rare Kidney Disease Reference Network (ERKNet) recently established ERKReg, a Web-based registry for all patients with rare kidney diseases. The main objectives of this core registry are to generate epidemiological information, identify current patient cohort for clinical research, explore diagnostic and therapeutic management practices, and monitor treatment performance and patient’s outcomes. The registry has a modular design that allows to integrate comprehensive disease-specific registries as extensions to the core database. The diagnosis (Orphacode) and diagnostic information (clinical, imaging, histopathological, biochemical, immunological and genetic) are recorded. Anthropometric, kidney function, and disease-specific management and outcome items informing a set of 61 key performance indicators (KPIs) are obtained annually. Data quality is ensured by automated plausibility checks upon data entry and regular offline database checks prompting queries. Centre KPI statistics and benchmarking are calculated automatically.